OPTIMIZATION OF TRANSPORT AND LOGISTICS PROCESSES OF INDUSTRIAL ENTERPRISE - Khalipova, N. V.; Lesnikova, I. Yu.; Israfilova, N. A. (Systems and Technologies, 2018)
Analysis of transport-logistical processes of the enterprise at the presentstage showed uneven condition and certain disproportions in their development.Was discovered that the problem is complex and one of the important drawbacksis the inefficient allocation and use of the existing transportation f leet. It isestablished that for the development of an industrial enterprise an importantaspect is the organization of efficient transport and logistics processes, theplanning of which should use the general principles, such as full satisfaction ofenterprise structural units transport needs, efficient use of technical means anddifferent types of resources, consideration of work of all types of transport in complex. he analysis shows that when planning the work of transport, the mostdifficult area is operational planning, whose functions are to establish agreedvolumes of transport work and their units in the near future, routing oftransportation, organization and coordinated work of transport and structuralunits of the enterprise. Continuous production at the enterprise requires constantprompt updating of existing solutions for transport and logistics support andwarehouse solutions.To solve the problem of given production situation, it is proposed to use amulti-stage algorithm, which includes a sequential tasks solution: linearprogramming with limitations on the resources of the enterprise; the transporttask and the task of the shortest distance from suppliers to warehouses fortransportation of specified volumes of raw materials with the least cost; furtherformulation of conclusions and recommendations regarding the solutionimprovement and making the final decision. Microsoft Excel „Solution Finder‟plugin was used to solve our optimization tasks.On the example of PrJSC Metinvest holding, an analysis of the existingtransport and logistics support was carried out and the optimal raw materialsupply schemes were determined to ensure the operation of the resin-processingmanufactory department. For continuous operation of the resin-processingdepartment, it is necessary to have appropriate capacities for raw materialsstoraging. Based on the analysis of optimal raw material delivery schemes tosupport manufactoring, storage tanks capacity and the optimal delivery schedulesfor coal tar have been identified.The results of the study indicate the need for continuous prompt updating ofexisting solutions and can be used to improve the transport and logisticscomponent of industrial enterprise processes.